Novel insight into uPAR function in the bronchial epithelium in asthma using functional genomics - Bhaker, Sangita (2017)
The urokinase plasminogen activator receptor (uPAR, PLAUR) is a cell surface receptor actively involved in the regulation of cell homeostasis. Expression is elevated in the bronchial epithelium in vivo and also in serum and sputum in asthma and elevated expression often indicates poor prognosis in a number of human diseases. The relative contribution of uPAR to asthma disease mechanisms is not fully understood and the functional roles of uPAR isoforms remains to be resolved. The key aims of this thesis were to i) investigate how the uPAR pathway may influence bronchial epithelial barrier properties; ii) investigate the gene expression patterns in the bronchial epithelium in asthma; iii) identify functions of different forms of uPAR in human bronchial epithelial cells (HBEC) and to iv) investigate the association between genetic polymorphisms spanning the PLAUR gene with clinical features and the presentation of asthma in moderate to severe asthma.